CONTEMPORARY ENDODONTIC OBTURATION TECHNIQUES: A COMPREHENSIVE LITERATURE REVIEW - Arzu Şeyma Demir; Recai Zan (Cumhuriyet University, 2021)
The success of an endodontic treatment is excessively depends on obturation as well as irrigation. Hence, achiving a homogenious, impermeable and gap-free obturation plays a crucial role in endodontic treatment. Today, many materials and techniques have been developed for endodontic purpose such as those which applied with heat or vibration, those softened with non-toxic chemicals and those uses ultrasound energy. Some of these techniques are still preferred by proffessionals when some are abandoned. However, gutta-percha is the most used material either with or without sealer. Gutta-percha can be applied with cold or warm techniques. It's known that warm gutta-percha technique leads a more homogenious obturation than cold techniques. Nevertheless, different obturation methods are convenient for different anatomic variations of root canal system. This review article summerize the contemporary and conventional obturation techniques with evaluation of their current status in endodontic implementation.